2021
DOI: 10.1183/23120541.00941-2020
|View full text |Cite
|
Sign up to set email alerts
|

The isobaric pulmonary arterial compliance in pulmonary hypertension

Abstract: Pulmonary hypertension (PH) is associated with stiffening of pulmonary arteries which increases right ventricular pulsatile loading. High pulmonary artery wedge pressure (PAWP) in postcapillary PH (Pc-PH) further decreases PA compliance (PAC) at a given pulmonary vascular resistance (PVR) compared to precapillary PH, thus responsible for a higher total arterial load. In all other vascular beds, arterial compliance is considered as mainly determined by the distending pressure, due to non-linear stress-strain be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Some authors have suggested that the mPAP versus sPAP linear relationship reflects the constancy or near‐constancy of the time constant of the pulmonary Windkessel, as quantified by the pulmonary vascular resistance times PA compliance product 36,37 . This explanation has been recently ruled out because the value of the time constant of the pulmonary Windkessel is not constant but on the contrary more variable than mPAP in patients with either precapillary or postcapillary PH 38 . In other words, to continue to support the constancy or near‐constancy of the time constant of the pulmonary Windkessel would be as unrealistic as supporting that mPAP is constant or near‐constant in PH states 38 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some authors have suggested that the mPAP versus sPAP linear relationship reflects the constancy or near‐constancy of the time constant of the pulmonary Windkessel, as quantified by the pulmonary vascular resistance times PA compliance product 36,37 . This explanation has been recently ruled out because the value of the time constant of the pulmonary Windkessel is not constant but on the contrary more variable than mPAP in patients with either precapillary or postcapillary PH 38 . In other words, to continue to support the constancy or near‐constancy of the time constant of the pulmonary Windkessel would be as unrealistic as supporting that mPAP is constant or near‐constant in PH states 38 .…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 This explanation has been recently ruled out because the value of the time constant of the pulmonary Windkessel is not constant but on the contrary more variable than mPAP in patients with either precapillary or postcapillary PH. 38 In other words, to continue to support the constancy or near‐constancy of the time constant of the pulmonary Windkessel would be as unrealistic as supporting that mPAP is constant or near‐constant in PH states. 38 One hypothesis may be that the redundancy between mPAP and sPAP is explained by the fact that changes in PA stiffness are primarily due to increases in mPAP under both experimental and clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations